Come be my lover - Stereo Nation; Viper Records; EMI Records (United Kingdom : Viper Records, 1996)
Contains two pop mixed tracks.
Come Be My Lover (radio edit) -- Come Be My Lover (Euro mix).
Koleksi Khas Wiramanja.
Group members : Kendell Smith, Tarsame'Taz' Singh.
Title from disc label.
Keywords: Songs, English; Reggae music